International Monetary Fund Annual Report 2010 : Financial Statements. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents the IMF financial statements for 2009-10. The paper highlights that the consolidated financial statements of the General Department are prepared in accordance with International Financial Reporting Standards issued by the International Accounting Standards Board. They have been prepared under the historical cost convention, except for the revaluation of financial assets at fair value through profit and loss. The consolidated financial statements are presented in Special Drawing Rights, which is the IMF's functional unit of account.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet